The Effectiveness of the Solution-Focused Brief Counseling Approach to Increase Social Awareness in Class VIII A Students at Enrekang 2 Public Middle School - Mawaddatul Maykam; Muhammad Junaedi Mahyuddin; Aisyah Suryani; Fitriyanti Sulaiman; M. Yunus Sudirman (Universitas Muhammadiyah Enrekang, 2023)
Social awareness is a process in which a person understands and understands a situation that makes the individual himself aware and understands very well what is happening and what will happen. Facts on the ground show that students at SMP Negeri 2 Enrekang have experienced a decline in social awareness. This is why researchers offer solutions to increase students' social awareness by using SFBC counseling (solution-focused brief counseling). The use of this approach places more emphasis on short counseling times and has a lot of research that proves its effectiveness. The purpose of this study was to determine the application of the approach and the effectiveness of the solution-focused brief counseling approach in increasing social awareness among students at SMP Negeri 2 Enrekang. The research method used in this study is a quantitative research method with a one group pretest-posttest research design. The sample used in this study were 10 students in class VIII A at SMP Negeri 2 Enrekang. The results showed that the use of the SFBC approach with the scaling question technique had an effect on increasing students' social awareness compared to without using the SFBC approach with the scaling question technique.